Políticas públicas para erradicar el trabajo infantil en el cantón Tulcán - Romo Montenegro, Edison David (2024)
This research was conducted on public policies dedicated to eradicating child labor in the canton of Tulcán. Child labor is a problem that occurs in Ecuador, which is itself a country that guarantees rights and has the power to solve this type of situation through the issuance of public policies. Child labor is an activity that violates the rights of children and adolescents. The general objective was to identify public policies aimed at eradicating child labor in the canton of Tulcán through a documentary and field review in order to verify whether or not they are being effective. The approach used was qualitative, its research level was descriptive, the methods used were analytical, normative and socio legal, which allowed us to examine the information obtained through the technique of documentary review, interview and field observation resulting in the rights that child labor violates are the right to health, comprehensive protection and education. Similarly, it was found that in the canton of Tulcán there is no public policy focused on the eradication of child labor, there is only a public-private foundation dedicated to mitigate child labor. Finally, it is suggested that the competent authorities carry out plans or programs that are effective and efficient, as well as that the Municipal Government of Tulcán through the Cantonal Board for the Protection of Rights elaborate public policies through ordinances to eradicate child labor in the canton of Tulcán.